PAI Teacher's Strategy in Developing Students' Seeing, Listening and Feeling Skills at SMP Pahlawan Nasional Medan - Tarigan, Rizky Intan Sari; Mardianto, Mardianto Mardianto (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This study aims to identify the strategies used by Islamic Religious Education (PAI) teachers in developing the skills of seeing, hearing, and feeling students at SMP Pahlawan Nasional Medan. This study uses a descriptive descriptive approach by collecting data through interviews and observations of Islamic education teachers and students. The results of the study show that PAI teachers use various strategies, such as hands-on practice, group discussions, the Jigsaw method, and awarding to motivate students in learning. The media used include text books, Al-Qur'an, posters, and video presentations. Evaluation is carried out through direct practice, giving awards, and assessing student performance. The obstacles faced by PAI teachers include variations in students' ability levels and the influence of gadgets. Nonetheless, the strategies and methods applied by PAI teachers have succeeded in developing the skills of seeing, hearing, and feeling students, and can be applied in everyday life. This research provides a better understanding of skills development strategies through PAI learning and provides insights for PAI teachers in increasing the effectiveness of learning.